Chueca / J. Nicolás Ferrando, Rocío Córdoba Pérez ; [prólogo, Pedro Zerolo ; escriben, Perico Echevarría, Juan Carlos Alonso, Jesús Encinar, Federico Armenteros, Carla Antonelli, Antonio Miguel Carmona] - Córdoba Pérez, RocíoEchevarría, Perico; Nicolás Ferrando, J.
Bibliografía: p. 181